Safety and efficacy of nebulised anti-inflammatory solution of alkaline hypertonic Ibuprofen (AHI) for treatment of SARS-Cov-2 Infection: A compassionate study with a comparator arms - Kalayan, Galia (2022)
This retrospective study evaluates the efficacy of inhalation therapy with alkaline hypertonic ibuprofen (AHI) inCOVID-19 positive patients compared to a control group of patients who received conventional treatment. The study was carried outat the Orías Hospital in Jujuy Province, Argentina, from June to September 2020, with final follow-up on September 30. Methods. Thestudy included 99 COVID-19 positive patients with moderate to severe disease (respiratory distress and/or hypoxemia). The controlgroup of 62 patients were treated with the protocols in force at that time, oxygen, dexamethasone and enoxaparin. The group underevaluation comprised 37 patients treated with AH), in addition to standard treatment. Findings. Result shows that the treatment withAHI formulation is safe and effective. The mean respiratory rate (RR) of the patients went from 26.3 before treatment with AHI to19.8 after treatment. On the other hand, the O2 saturation of patients before treatment with AHI showed a mean of 89.0%; at the end oftreatment, the mean was 95.8%. In patients treated with AHI, on day 14, 85% had been discharged, while in patients not treated withAHI, only 36-37% were discharged on day 23. Patients with standard treatment, without AHI, show a mortality of 38.7%, distributedevenly in the 25 days of hospitalization. The mortality of patients treated with AHI was 8.1%, observed within the first 10 days of hospitalization. Interpretation. Results show that nebulization with AHI is an anti-inflammatory therapeutic alternative for the treatmentof COVID-19 positive patients.